2023
DOI: 10.1002/imt2.125
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in heart failure and related interventions

Abstract: Heart failure (HF) is a sophisticated syndrome with structural or functional impairment of ventricular filling or ejection of blood, either causing symptoms and signs or being asymptomatic. HF is a major global health issue affecting about 64.3 million people worldwide. The gut microbiota refers to the complex ecosystem of microorganisms, mainly bacteria, in the gut. Studies have revealed that the gut microbiota is associated with many diseases ranging from neurodegenerative diseases to inflammatory bowel dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…They reside on intestinal epithelial barriers and are symbiotic with the host. The complex microbial ecosystem is crucial in human health, and disruption of which is associated with chronic inflammation, auto‐immune diseases, heart failure, and even cancer [ 8 , 9 ] (Figure 2 ). Previous studies have indicated commensal microbiota plays contrasting roles in cancer initiation, progression, and metastasis.…”
Section: The Cancer‐microbiota‐immune Axismentioning
confidence: 99%
“…They reside on intestinal epithelial barriers and are symbiotic with the host. The complex microbial ecosystem is crucial in human health, and disruption of which is associated with chronic inflammation, auto‐immune diseases, heart failure, and even cancer [ 8 , 9 ] (Figure 2 ). Previous studies have indicated commensal microbiota plays contrasting roles in cancer initiation, progression, and metastasis.…”
Section: The Cancer‐microbiota‐immune Axismentioning
confidence: 99%